Russian gastroenterological association clinical guidelines on diagnostics and treatment of NSAIDs-associated erosive and ulcerative lesions of the stomach and duodenum - V. T. Ivashkin; A. A. Sheptulin; I. V. Mayev; Ye. K. Baranskaya; A. S. Trukhmanov; T. L. Lapina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.